Improvement of the Ukrainian Labor Legislation in the Context of European Integration - Klietsova, Nataliia (Research Papers, 2018)
The article studies current practice of Ukraine’s labor legislation regarding the hired workers’ recruitment. The research task is to present the process of improvement of the Ukrainian labor legislation in this field in the context of European integration. The methodical approach is a comparative analysis of the economic and legal aspect of the hired workers’ employment protection. The paper here presented is an original one.
Keywords: Labor legislation; Employee; Employment; Gross salary; Criminal responsibility